Effects of camptothecin derivatives and topoisomerase dual inhibitors on Trypanosoma cruzi growth and ultrastructure - Lacombe, Otto Kischlat (BioMed Central, 2014)
BACKGROUND: Trypanosoma cruzi is the etiological agent of Chagas’ disease that is an endemic disease in Latin America and affects about 8 million people. This parasite belongs to the Trypanosomatidae family which contains a single mitochondrion with an enlarged region, named kinetoplast that harbors the mitochondrial DNA (kDNA). The kinetoplast and the nucleus present a great variety of essential enzymes involved in DNA replication and topology, including DNA topoisomerases. Such enzymes are considered to be promising molecular targets for cancer treatment and for antiparasitic chemotherapy. In this work, the proliferation and ultrastructure of T. cruzi epimastigotes were evaluated after treatment with eukaryotic topoisomerase I inhibitors, such as topotecan and irinotecan, as well as with dual inhibitors (compounds that block eukaryotic topoisomerase I and topoisomerase II activities), such as baicalein, luteolin and evodiamine. Previous studies have shown that such inhibitors were able to block the growth of tumor cells, however most of them have never been tested on trypanosomatids. RESULTS: Considering the effects of topoisomerase I inhibitors, our results showed that topotecan decreased cell proliferation and caused unpacking of nuclear heterochromatin, however none of these alterations were observed after treatment with irinotecan. The dual inhibitors baicalein and evodiamine decreased cell growth; however the nuclear and kinetoplast ultrastructures were not affected. CONCLUSIONS: Taken together, our data showed that camptothecin is more efficient than its derivatives in decreasing T. cruzi proliferation. Furthermore, we conclude that drugs pertaining to a certain class of topoisomerase inhibitors may present different efficiencies as chemotherapeutical agents.